A new physics‐based modeling approach for tsunami‐ionosphere coupling. Issue 12 (30th June 2015) - Meng, X.; Komjathy, A.; Verkhoglyadova, O. P.; Yang, Y.‐M.; Deng, Y.; Mannucci, A. J.
Abstract Tsunamis can generate gravity waves propagating upward through the atmosphere, inducing total electron content (TEC) disturbances in the ionosphere. To capture this process, we have implemented tsunami‐generated gravity waves into the Global Ionosphere‐Thermosphere Model (GITM) to construct a three‐dimensional physics‐based model WP (Wave Perturbation)‐GITM. WP‐GITM takes tsunami wave properties, including the wave height, wave period, wavelength, and propagation direction, as inputs and time‐dependently characterizes the responses of the upper atmosphere between 100 km and 600 km altitudes. We apply WP‐GITM to simulate the ionosphere above the West Coast of the United States around the time when the tsunami associated with the March 2011 Tohuku‐Oki earthquke arrived. The simulated TEC perturbations agree with Global Positioning System observations reasonably well. For the first time, a fully self‐consistent and physics‐based model has reproduced the GPS‐observed traveling ionospheric signatures of an actual tsunami event.